Communicating with deaf children : exploring the experiences of hearing parents. - Klein, Amanda (My University, 2010)
This study examines the experiences of hearing parents of deaf children and the process by which they come to choose a primary communication mode to use with their deaf children. Among the many obstacles that parents face in connection with their deaf child’s diagnosis of deafness, communication considerations appear most prominent, with choice of communication modality often emphasised. Participants in this study were hearing parents whose children attended St. Vincent School for the Deaf in Melrose, Johannesburg. Seven participants were interviewed using a semistructured approach. Interviews were transcribed and then analysed using thematic content analysis. Data analysis yielded three main themes with various sub-themes falling underneath these. The first theme identified was ‘Diagnosis of Deafness’ under which fell ‘Reaction of Parents to Diagnosis’ and ‘Information Provided by Professionals Consulted’. The second theme identified was ‘Mode of Communication’ which subsumed three sub-themes, namely; ‘Primary Mode of Communication used’, ‘Important Referent’s Views on Preferred Mode of Communication’ and ‘Lack of Communication’. The third theme identified was ‘Stigma’. Under the theme ‘stigma’ fell two sub-themes, namely; ‘Treatment by Hearing Children’ and ‘Perceptions of Deaf People’. Conclusions and implications of these themes for service provision are discussed.